The impact of ICT on the development of children's religious and moral values - Hardiyana, Andri; Dwiyanti, Intan; Zakiyah, Ishmatun; Munafiah, Nida'ul (Universitas Islam Negeri Raden Intan Lampung, 2022)
Human civilization today cannot be separated from the development of information and communication technology. The purpose of this study was to describe and analyze the impact of the use of information and communication technology on the development of early childhood religious and moral values. The results of this study indicate that the use of ICT has a positive and negative impact, especially the psychological impact on children's development. In addition, the use of ICT, if it can be used wisely, can lead to a) the right to education through the use of ICT under parental supervision, b) the role of parents in education, supervision, and control of children in the use of ICT, c) facilitate parents and children in learning and communication, d) can grow aspects of child development comprehensively, e) as a media for children to learn characters in a game/video, f) helping children listen to murotal or g) as a reminder (alarm) when worshiping/doing essential activities. The findings of the adverse effects of this study caused: a) children sometimes spoke harshly, b) children became quiet and lacked socialization with the surrounding environment, and c) lost track of time.